2013
DOI: 10.1530/eje-13-0148
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of LB03002, a once-weekly sustained-release human GH for 12-month treatment in Korean children with GH deficiency

Abstract: Purpose: The purpose of this study was to investigate the efficacy and safety of LB03002, a sustainedrelease human GH (SR-hGH), compared with that of daily rhGH for 12 months in children with GH deficiency (GHD). Methods: A total of 73 children with GHD were screened and 63 eligible subjects were randomized in a 1:1 ratio of LB03002 (SR-hGH) to daily rhGH treatment group. LB03002 was administered once weekly at a dose of 0.5 mg/kg while daily rhGH was administered for 6 consecutive days with equally divided do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
0
8
1
Order By: Relevance
“…A total of 1,245 unique studies were identified, of which 11 studies (between 2012 and 2021) fulfilled the inclusion criteria and were included in the study (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1,245 unique studies were identified, of which 11 studies (between 2012 and 2021) fulfilled the inclusion criteria and were included in the study (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…The safety profile of our PEG-rhGH was mostly consistent with previous reports of long-acting rhGH (9, 10, 11, 12). Our study did show higher incidence of peripheral edema associated with PEG-rhGH vs daily rhGH, while previous studies on LB03002 and Neutropin Depot did not report increased incidence of peripheral edema in pediatric patients with GHD (2, 11, 12, 21). In our study, most incidences of edema experienced by patients were mild and resolved themselves without treatment interruption.…”
Section: Discussioncontrasting
confidence: 82%
“…The first plausible explanation is that the LB03002 dose (0.5 mg/kg/week) might not have been high enough to improve the HV of children with ISS. In the previous phase III trial of Korean GHD patients [15], HV achieved after administration of LB03002 at 0.5 mg/kg/week was not inferior to that obtained with daily rhGH 0.21 mg/kg/week. This implies that a higher dose (0.7 mg/kg/week) of LB03002 should be considered for children with ISS.…”
Section: Discussionmentioning
confidence: 78%